2000
DOI: 10.1046/j.1365-2249.2000.01326.x
|View full text |Cite
|
Sign up to set email alerts
|

Study of antibody and T cell responses in rabbits immunized with synthetic human B cell epitope analogues of La (SSB) autoantigen

Abstract: SUMMARYThe aim of this study was to investigate the immunogenicity of four synthetic peptides, representing linear B cell epitopes of the human La/SSB autoantigen: 145±164 aa (p1), 289±308 aa (p2), 301±318 aa (p3) and 349±364 aa (p4), in rabbits. New Zealand White rabbits were immunized with each of the above peptides attached in four copies on tetrameric sequential oligopeptide carriers (SOC) in duplicate. Control immunizations were also performed (one rabbit each, immunized with Freud's complete adjuvant alo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0

Year Published

2001
2001
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 27 publications
2
29
0
Order By: Relevance
“…Moutsopoulos et al recently analyzed the antibody production and the T-cell response in rabbits immunized with peptide 145±164 of La which contains the RNP1 motif. In good agreement with the proposed model, they demonstrated that immunization with peptide 145±164 induced spreading of T-cell responses to seven other peptides of the protein [65]. This was not observed to the same extend with the other peptides.…”
Section: Key Sequences Involved In the Spreading Of The Systemic Autosupporting
confidence: 76%
“…Moutsopoulos et al recently analyzed the antibody production and the T-cell response in rabbits immunized with peptide 145±164 of La which contains the RNP1 motif. In good agreement with the proposed model, they demonstrated that immunization with peptide 145±164 induced spreading of T-cell responses to seven other peptides of the protein [65]. This was not observed to the same extend with the other peptides.…”
Section: Key Sequences Involved In the Spreading Of The Systemic Autosupporting
confidence: 76%
“…Although Ro60 protein possesses RRM domains, the degree of their sequence similarity with RRMs of the components of the U1-RNP complex is lower compared with La/SSB autoantigen. Moreover, the conserved sequence of the RRM of La/SSB has been previously characterized in our laboratory as B-cell/ T-cell epitope associated with SLE (14,22).…”
Section: Discussionmentioning
confidence: 99%
“…The homologous region of La/SSB (aa145-164) had been previously characterized by our group as an SLE-associated B-cell epitope (14), serving also as a T-cell epitope (22) …”
Section: S P R E a D I N G O F A U T O I M M U N E R E S P O N S E V mentioning
confidence: 99%
“…La/SSB is phosphorylated primarily at the serine 366 amino acid residue, resulting in inhibition of the polymerase III transcription factor activity of the protein; this chemical modification results in the decreased ability of the molecule to bind and protect the 5′ end of nascent RNA molecules [23]. In our laboratory the major linear B cell epitope of the molecule has been defined previously in the amino acid region 349-368aa of the protein [24,25]. The phosphorylated form of this epitope was found to be recognized more frequently and with a higher relative avidity by autoantibodies derived from sera of patients with pSS [26], compared with the unmodified form of the epitope.…”
Section: Discussionmentioning
confidence: 97%